THE DIFFICULTIES OF PHYSICAL EDUCATION TEACHERS WHO TEACH MUNICIPAL SCHOOL OF GOOD DRESS IN 1ST GRADE A 4. (Fiep Bulletin - online, 2014)
Contribute to the appreciation of the Physical Educator locally is the overall goal of this work, which includes, among others, incite new research and inform the public and academic teaching; valuing teachers in their educational activity, set up a new vista for the discursão issues discussed. With the following title "The Difficulties of Teacher Of Physical Education from 1st to 4th Series in That Affect School District Boa Vista" work Formulated as a problem situation "assess whether there obstacles and difficulties to the educational practice of Educators Physicists working the municipal education teaching 1st through 4th grades. We emphasize that it is still possible to find in this article what the National Curricular Parameters - PCN's - suggest about objectives, content and evaluation of physical education for first to fourth graders regular; relations compromise between workand worker hierarchies and needs: motivation x salary. In a second step we research field and its developments. This research was conducted through a questionnaire and had as its object the Physical Education Teachers Network Municipal Education toteach from 1st to 4th grades. Applied with 24 professional research conclusions obtained such as the poor quality sporting goods and also insufficient regarding the amount, about 46% of respondents had experienced some form of discrimination training.Therefore, this article is configured as an important source of research and consultation activities of labor Physical Educator of the municipal Physical Education Good view.
Keywords: Education; teacher; difficulties; materials; motivation and remuneration.